Method Development and Validation for the Simultaneous Estimation of Diphenhydramine, Ephedrine, Noscapaine, Glycerol Glycolate in Bulk and in Tablets by Using RP-HPLC - Pulagurtha Bhaskararao; Kontham Venkataramanapa Raju (Novel Aspects on Pharmaceutical Research Vol. 1, 2023)
The present investigation highlights the development and validation of a reverse phase high performance liquid chromatographic (RP-HPLC) method to quantify DH, ED, NP and GG simultaneously in bulk and in fixed dosage form, Noscof. Noscof Tablet is used to manage and relieve symptoms of allergy, hay fever, common cold, asthma, low blood pressure, prostate cancer, heart attack, diarrhea, encephalitis, Meningitis, Reye’s syndrome, and dry cough. RP-HPLC for the simultaneous estimation of DH, ED, NP and GG was done on an Altima C18 column with 0.01M KH2PO4 buffer (PH 3.5) and Acetonitrile (50%, v/v) as mobile phase at 0.8 ml/min flow rate in an isocratic mode at 260 nm and method was validated according to ICH guidelines. The tablet sample solution was subjected to diverse stress conditions using ICH strategy like hydrolytic degradation i.e. Neutral medium- with distilled water, Alkaline medium– with 2N NaOH and Acidic medium– with 2N HCl, oxidative degradation with 10% H2O2, photo degradation by exposing to UV light and dry heat degradation by exposing to 105oC. Using the above stated chromatographic conditions, sharp peaks were obtained for ED, NP, DH and GG with retention time of 3.272 min, 4.098 min, 5.467 min and 6.783 min respectively. Good regression coefficients values were obtained in the range of 2-12 µg/ml for ED, 3.75-22.5 µg/ml for NP, 3.125-18.75 µg/ml for DH and 25-150 µg/ml for GG. The QLs were 0.181 µg/ml, 0.187 µg/ml, 0.246 µg/ml and 1.114 µg/ml for ED, NP, DH and GG, respectively. The values of validation parameters are within the acceptable limits of ICH guidelines. The ED, NP, DH and GG had shown higher percentage of degradation in acidic medium and less percentage of degradation in neutral medium. The peaks of degradants did not interfere with the peaks of analytes. ED, NP, DH and GG were assessed with good percentage of assay (near to 100%) and low percent relative standard deviation (<2%) in Noscof tablets using the proposed method. The RP-HPLC method developed was validated and was found to be suitable for the quantification of ED, NP, DH and GG simultaneously in bulk as well as in tablet dosage form.